The Value and Performance of Islamic Banking in Indonesia - Zulfikar Hasan (IQTISHADIA, 2022)
This study aimed to examine the value of Indonesian Islamic banking using secondary quarterly data from quarter I of 2016 to quarter IV of 2021. The data were sourced from Sharia Banking Statistics (SPS) published by the Financial Services Authority (OJK). EViews 8 was then used to analyze economic growth with financing distributed by Islamic banking. Furthermore, the study employed a qualitative method assisted with data from OJK. The findings showed that the value, growth, and development of Islamic banking in Indonesia are better than conventional banking. Also, the profitability ratio of Indonesian Islamic banking is categorized as good. The value of Islamic banking can be analyzed using several components such as growth, risk, returns and capital and cost.